Stakeholders' Guidance Document for Consumer Analytical Devices with a Focus on Gluten and Food Allergens. (23rd November 2019) - Popping, Bert; Allred, Laura; Bourdichon, François; Brunner, Kurt; Diaz-Amigo, Carmen; Galan-Malo, Patricia; Lacorn, Markus; North, Jennifer; Parisi, Salvatore; Rogers, Adrian; Sealy-Voyksner, Jennifer; Thompson, Tricia; et al.
Abstract: Until recently, analytical tests for food were performed primarily in laboratories, but technical developments now enable consumers to use devices to test their food at home or when dining out. Current consumer devices for food can determine nutritional values, freshness, and, most recently, the presence of food allergens and substances that cause food intolerances. The demand for such products is driven by an increase in the incidence of food allergies, as well as consumer desire for more information about what is in their food. The number and complexity of food matrixes creates an important need for properly validated testing devices with comprehensive user instructions (definitions of technical terms can be found in ISO 5725-1:1994 and the International Vocabulary of Metrology). This is especially important with food allergen determinations that can have life-threatening consequences. Stakeholders—including food regulators, food producers, and food testing kit and equipment manufacturers, as well as representatives from consumer advocacy groups—have worked to outline voluntary guidelines for consumer food allergen- and gluten-testing devices. These guidelines cover areas such as kit validation, user sampling instructions, kit performance, and interpretation of results. The recommendations are based on ( 1 ) current known technologies, ( 2 ) analytical expertise, and ( 3 ) standardized AOAC INTERNATIONAL allergen community guidance and best practices on the analysis of food allergens and gluten. The present guidance document is the first in a series of papers intended to provide general guidelines applicable to consumer devices for all food analytes. Future publications will give specific guidance and validation protocols for devices designed to detect individual allergens and gluten, as statistical analysis and review of any validation data, preferably from an independent third party, are necessary to establish a device's fitness-for-purpose. Following the recommendations of these guidance documents will help ensure that consumers are equipped with sufficient information to make an informed decision based on an analytical result from a consumer device. However, the present guidance document emphasizes that consumer devices should not be used in isolation to make a determination as to whether a food is safe to eat. As advances are made in science and technology, these recommendations will be reevaluated and revised as appropriate.